2014
DOI: 10.4132/koreanjpathol.2014.48.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Transformation of Papillary Thyroid Carcinoma in a Young Man: A Case Study with Immunohistochemical andBRAFAnalysis

Abstract: This study reports a case of anaplastic transformation from a well-differentiated thyroid carcinoma in a young patient. The first recurrent tissue contained poorly differentiated foci that revealed lower thyroglobulin, thyroid transcription factor 1 (TTF-1), and galectin-3 expression than the well-differentiated area. However there was no increased p53 or Ki-67 expression in the poorly differentiated foci, nor in the well-differentiated area. The tissue subsequently relapsed and revealed only anaplastic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…All these mutations were previously reported, and they were not directly associated with the constitutive activation of the BRAF protein. But it is reported that BRAF F595L mutation is a gain-of-function variant with intermediate activity that does not act paradoxically, but cooperates with mutant RAS to promote oncogenic signalling [14,15].…”
Section: Original Papermentioning
confidence: 99%
“…All these mutations were previously reported, and they were not directly associated with the constitutive activation of the BRAF protein. But it is reported that BRAF F595L mutation is a gain-of-function variant with intermediate activity that does not act paradoxically, but cooperates with mutant RAS to promote oncogenic signalling [14,15].…”
Section: Original Papermentioning
confidence: 99%
“…It mostly develops from follicular derived differentiated thyroid cancers or directly from normal follicular thyroid cells [3]. In rare occasions, a papillary thyroid carcinoma can also transform to an anaplastic carcinoma as it was demonstrated in several case studies [4,5]. ATC has a heterogeneous mutational background.…”
Section: Introductionmentioning
confidence: 99%
“…Park JH et al reported a case of anaplastic transformation of PC in 23 years old man while Abe T et al recorded similar findings in a 61-year-old male. 20 , 21 Thyroid carcinoma metastasis to the skull bone is rare and is found in only 2.5% to 5.8% cases of thyroid carcinoma. Li X et al in their study reported PC metastasis to the skull in 61 years old female.…”
Section: Discussionmentioning
confidence: 99%